2021
DOI: 10.1158/1078-0432.ccr-21-2001
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Pembrolizumab in Combination with Doxorubicin in Metastatic and Unresectable Soft-Tissue Sarcoma

Abstract: Purpose: Doxorubicin is standard therapy for advanced soft-tissue sarcoma (STS) with minimal improvement in efficacy and increased toxicity with addition of other cytotoxic agents. Pembrolizumab monotherapy has demonstrated modest activity and tolerability in previous advanced STS studies. This study combined pembrolizumab with doxorubicin to assess safety and efficacy in frontline and relapsed settings of advanced STS. Patients and Methods: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Patients with a complete or partial response are indicated in green, those with progressive disease in red, and those with stable disease in yellow Chemotherapy combined with a PD-1 inhibitor has been shown to have a beneficial effect against various other malignancies [20,25,29]. Recent clinical trials have demonstrated the efficacy and safety of the combination of the PD-1 inhibitor, pembrolizumab, and the chemotherapy drug, doxorubicin, for treating patients with advanced STS [22,30]. These results suggest that it is feasible to improve the sensitivity of PD-1 inhibitors by combining them with chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a complete or partial response are indicated in green, those with progressive disease in red, and those with stable disease in yellow Chemotherapy combined with a PD-1 inhibitor has been shown to have a beneficial effect against various other malignancies [20,25,29]. Recent clinical trials have demonstrated the efficacy and safety of the combination of the PD-1 inhibitor, pembrolizumab, and the chemotherapy drug, doxorubicin, for treating patients with advanced STS [22,30]. These results suggest that it is feasible to improve the sensitivity of PD-1 inhibitors by combining them with chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent evidence shows that the response rate of PD-1 inhibitor monotherapy is low in patients with STS [17,18], there have been encouraging reports of efficacy in some sarcoma subtypes [19]. The combination of PD-1 inhibitors with cytotoxic chemotherapy agents is a promising way to improve the efficacy of PD-1 inhibitors in the treatment of patients with malignant tumors, including STS [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Two clinical trials evaluating the efficacy of doxorubicin with pembrolizumab had promising results, one with an ORR of 36.7%. 34,35 ICI in combination with trabectedin has also demonstrated clinical activity, with an ORR of 19.5%, including 3 complete responses. 36 Combining ICI with tyrosine kinase inhibitors was evaluated in ImmunoSarc, which evaluated the safety and efficacy of sunitinib and nivolumab in advanced STS.…”
Section: Ici and Systemic Therapymentioning
confidence: 98%
“…Other commonly used cytotoxic therapies in sarcomas, including gemcitabine, trabectedin, and eribulin, also have pro-immunogenic effects. Gemcitabine suppresses MDSCs within other cancer subtypes [84] , trabectedin has been shown to diminish the production of immunosuppressive cytokines in myxoid liposarcomas [85] , and eribulin helps to remodel aberrant tumor blood vessels in murine mouse models [86] . In hopes of providing a source of immunogenic neoantigens and pro-inflammatory mediators for poorly immunogenic sarcomas, multiple studies exploring chemotherapy with checkpoint inhibitors have been recently reported or are ongoing.…”
Section: Chemotherapy Combinationsmentioning
confidence: 99%
“…No additional phenotyping was reported to explain this surprising finding. More recently, Livingston et al [ 87 ] reported an overall response rate of 36.7%, median PFS of 5.7 months, and a 6 month PFS rate of 44%, in 30 patients with advanced soft tissue sarcomas. Interestingly, analysis of PD-L1 expression in 29 of the 30 patients revealed an association of high PD-L1 expression with objective response rate, however, did not correlate with PFS or overall survival.…”
Section: Emerging Mechanisms Of Resistancementioning
confidence: 99%